Plantation Sector in Central Kalimantan Province: Optimization of Production Factor Use - Pratama, Rian; Suluh, Siang I; Sabirin, Sabirin (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2023)
The objective of this study is to examine the impact of labor and capital utilization on production value within the plantation sector in Central Kalimantan Province. Additionally, it seeks to identify strategies for optimizing the use of labor and capital in this sector within the province. This particular research methodology falls under the category of explanatory research, which aims to examine the relationship between hypothesized variables and evaluate corresponding hypotheses. This study employs secondary data from various sources to examine the capital, labor, and production values in the plantation sector of Central Kalimantan Province over a 12-year period (2010-2021). The data sources include BPS Central Kalimantan Province, Ministry of Manpower and Transmigration, BKPMD, and other relevant sources. Based on the outcomes of the Multiple Linear Regression analysis conducted using SPSS version 25.0 (see attached), the findings of the analysis can be summarized as follows: The concurrent utilization of labor and capital in the plantation sector of Central Kalimantan Province has a notable and favorable impact on the output value. The optimization of labor and capital utilization in the plantation sector of Central Kalimantan Province from 2010 to 2021 has not consistently achieved optimal levels. There were periods where the utilization was above the optimum level, while in other years it fell below the optimum level